Addressing Irregular Migration through Principled Programmatic Approaches: Examining the West Africa Route - Moussavi, Sara; de Brauw, Alan; Williams, Sarah (2023)
Sara Moussavi (WFP), Alan de Brauw (IFPRI), & Sarah Williams (MIT) VIRTUAL RESEARCH SEMINAR Irregular Migration and Food Security: A View from West Africa Co-organized by IFPRI and World Food Programme (WFP) JUL 20, 2023 - 9:30 TO 11:00AM EDT